Beyond Jewish Identity: Rethinking Concepts and Imagining Alternatives - Kelman, Ari Y; Levisohn, Jon A (Academic Studies Press, 2019)
Frontmatter -- Table of Contents -- Introduction / Levisohn, Jon A. / Kelman, Ari Y. -- Taking Jewish Identity Metaphors Literally / Gottlieb, Eli -- You are Jewish if You Want to Be: The Limits of Identity in a World of Multiple Practices / Mehta, Samira K. -- On the Origins and Persistence of the Jewish Identity Industry in Jewish Education / Krasner, Jonathan -- Identity and Crisis: The Origins of Identity as an Educational Outcome / Kelman, Ari Y. -- Regarding the “Real” Jew: Authenticity Anxieties Around Poland’s “Generation Unexpected” / Reszke, Katka -- Re-Thinking American Jewish Zionist Identity: A Case for Post-Zionism in the Diaspora (Based on the Writings of R. Menachem Froman) / Magid, Shaul -- Jewish Educators Don’t Make Jews: A Sociological Reality Check About Jewish Identity Work / Zelkowicz, Tali -- Beyond Language Proficiency: Fostering Metalinguistic Communities in Jewish Educational Settings / Benor, Sarah Bunin / Avineri, Netta -- Where is the Next Soviet Jewry Movement? How Identity Education Forgot the Lessons that Jewish Activism Taught / Kelner, Shaul -- Jewish Education as Initiation into the Practices of Jewishness / Levisohn, Jon A. -- Jewish Sensibilities: Toward a New Language for Jewish Educational Goal-Setting / Moore, Lee / Woocher, Jonathan -- Index